FAKTOR-FAKTOR YANG MEMPENGARUHI RESISTENSI PENGGUNA DALAM IMPLEMENTASI SISTEM AKUNTANSI AKRUAL - Miftahur Rahman; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2017)
The purpose of this study is to examine the factors influencing users’ resistance towards implementation of accrual accounting. Dependent variable in this study is users’ resistance. And independent variables are top management, technologies and sistems, colleague opinion, self efficacy and external issues. This relationships are examined by multiple regression analysis. The population in this study consists of all users’ of accrual accounting in Indonesia. The sample in this study are all users’ of accrual accounting in KPPN Semarang 1 and consists of compiler of financial reports. The total number of samples in this study were 134 samples. Data collected by questionnaire. Data analysis was performed by the descriptive statistic analysis, the classical assumption, and hypothesis test with multiple regression analysis. The result of this study shows that three independent variables, they are technologies and sistems, colleagues opinion and external issues have significant relationship in influencing users’ resistance towards accrual accounting. Top management and self efficacy have no significant relationship in influencing users’ resistance towards accrual accounting.